2006
DOI: 10.1038/sj.cdd.4401990
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of translation for hid, grim and sickle mRNAs in Drosophila

Abstract: Protein synthesis is inhibited during apoptosis. However, the translation of many mRNAs still proceeds driven by internal ribosome entry sites (IRESs). Here we show that the 5 0 UTR of hid and grim mRNAs promote translation of uncapped-mRNA reporters in cell-free embryonic extracts and that hid and grim mRNA 5 0 UTRs drive IRES-mediated translation. The translation of capped-reporters proceeds in the presence of cap competitor and in extracts where cap-dependent translation is impaired. We show that the endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Previous publications [8], [11] investigated the IRES activity of the 5′-UTR sequences in five Drosophila melanogaster protein-coding genes, rpr, hsp70, hid, grim and skl , as well as the IRES activity of the reverse complement of the 5′-UTR sequences. We analyzed the 60 nt segment immediately upstream of the initiation codon of these genes and their reverse complements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous publications [8], [11] investigated the IRES activity of the 5′-UTR sequences in five Drosophila melanogaster protein-coding genes, rpr, hsp70, hid, grim and skl , as well as the IRES activity of the reverse complement of the 5′-UTR sequences. We analyzed the 60 nt segment immediately upstream of the initiation codon of these genes and their reverse complements.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the strength of IRES activity of the fruit fly IRESs is also strongly associated with weak secondary structure (Figure 2, r = −0.8461, p = 0.001), consistent with the pattern observed with yeast data in Figure 1. The reverse complements of the 60 nt 5′-UTR sequences in the five fruit fly genes showed little or no IRES activity [8], [11] and all exhibited relatively stable secondary structure (Figure 2). The observation that the skl sequence with the least IRES activity also has the most stable secondary structure supports the general pattern (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other features such as long length of the 5′UTR (200 to 500 nucleotides), heavy RNA structure, high GC content, initiation at non-AUG codons, ignored AUGs upstream of the functional start codon are often but not universally found [46, 53, 76, 77]. For instance, some IRES elements found in plant RNA viruses, D. melanogaster and S. cerevisiae, have a high AU content [37, 62, 63, 73]. In this regard, the 5′UTR sequences of mRNAs are highly divergent [78].…”
Section: Ires Elements In Eukaryotic Organisms and Their Virusesmentioning
confidence: 99%